2022
DOI: 10.3389/fphys.2022.848867
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Curcumin in the Vasculature: A Therapeutic Candidate for Vascular Remodeling in Arterial Hypertension and Pulmonary Arterial Hypertension?

Abstract: Growing evidence suggests that hypertension is one of the leading causes of cardiovascular morbidity and mortality since uncontrolled high blood pressure increases the risk of myocardial infarction, aortic dissection, hemorrhagic stroke, and chronic kidney disease. Impaired vascular homeostasis plays a critical role in the development of hypertension-induced vascular remodeling. Abnormal behaviors of vascular cells are not only a pathological hallmark of hypertensive vascular remodeling, but also an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 220 publications
0
11
0
Order By: Relevance
“…Curcumin has been reported to exhibit vasodilating effects through the following possible mechanisms: (i) inhibition of angiotensin-converting enzyme via nuclear factor-kappa B activation and (ii) nitric oxide production via endothelial nitric oxide synthase activation. 24 The percentage change in systolic blood pressure from baseline to 6 months after initiating treatment was lower in the high-absorption curcumin group than in the placebo group ( P = 0.026). Therefore, the improvement in peripheral circulation by curcumin may be associated with the inhibition of an increase in BNP levels in patients with hypertension.…”
Section: Discussionmentioning
confidence: 91%
“…Curcumin has been reported to exhibit vasodilating effects through the following possible mechanisms: (i) inhibition of angiotensin-converting enzyme via nuclear factor-kappa B activation and (ii) nitric oxide production via endothelial nitric oxide synthase activation. 24 The percentage change in systolic blood pressure from baseline to 6 months after initiating treatment was lower in the high-absorption curcumin group than in the placebo group ( P = 0.026). Therefore, the improvement in peripheral circulation by curcumin may be associated with the inhibition of an increase in BNP levels in patients with hypertension.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study showed that curcumin provides vascular protection against arterial hypertension and PH. It can also improve hypertension and vascular remodeling by suppressing vasoconstriction, inhibiting vascular smooth muscle cell proliferation and migration, and improving endothelial cell dysfunction [ 95 ]. Curcumin protects mitochondrial function and promotes PASMCs apoptosis, thereby effectively reducing PAP and reversing pulmonary artery remodeling [ 96 ].…”
Section: Natural Products For the Treatment Of Phmentioning
confidence: 99%
“…Curcumin (CUR)—an active polyphenol extracted from the dried rhizomes of Curcuma longa —has been traditionally used for dietary and medical purposes worldwide ( Li KX. et al, 2022 ; Jin et al, 2022 ; Ojo et al, 2022 ).…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%